The material practices of quantification: Measuring 'deprivation' in the Amsterdam Neighbourhood Policy. (November 2016) - de Wilde, Mandy; Franssen, Thomas
The use of indicators and indexes in social policy, as part of evidence-based policy, is understood by governmentality scholars as 'techniques of governance'. However, we know very little about how the process of quantification is enacted in the material practices that constitute social policy itself. In this article we focus on a particular quantified object: the 'Normal Amsterdam Level' (NAP), used in an Amsterdam Neighbourhood Policy programme. We follow the NAP from its birth, to its life and its afterlife. We show that the qualification 'deprived' calls forth a whole set of problematic arrangements which are lost in a process of quantification . We understand the NAP as a generative device that actively assembles and arranges the world. These assemblages are rendered 'hard' through semiotic, statistical and visual techniques that produce facts about targeted neighbourhoods in relation to a city-wide average, thus serving as evidence and legitimisation for policy interventions.